The Military Brownfields, an Opportunity for the Urban Redevelopment of Small Mountain Towns? - Stéphanie Lotz-Coll (Revue de Géographie Alpine)
In a frame of limited land resources, mountain territories need to consider the reconversion of wastelands that have lost their functionality as potential source of attractiveness and dynamism.In a context of sustainable development that is also beginning to consider what could be the future activities that could mitigate the abandonment of small peripheral cities in terms of urban centrality, the brutal urban changes due to the recent departure of militaries from some small mountain garrison cities allow to consider a first return of experience regarding the redevelopment of military wastelands and the project engineering implemented to achieve this.After putting into context, the interest represented by wastelands, especially urban, for mountain territories, this article proposes a focus on the military wasteland, with, on the one hand, a reflexion on its trivialization and on the other hand, the context in which its reconversion could be considered as a success. A final part illustrates these elements in a concrete way with the recent reconversion of Barcelonnette and the Ubaye Valley.